The Polish language version of the Confusion Assessment Method – a questionnaire for the screening of consciousness disorders - Świerzy, Krzysztof A.; Pudlo, Robert; Wesołowski, Bartosz; Garbacz, Marcin; Morawski, Michał; Jaworska, Izabela; Sołtysik, Mariusz; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
Confusion on a somatic basis is a dangerous problem mainly related with aging of the population. Data says that consciousness disorders concern 10-15% of patients in general wards, and up to 50% of patients admitted to geriatric wards. The persistence of the symptoms of confusion results in increase of agitation, disorganization, fear, which increases the risk of self-injuries of patients, it causes the need for parenteral feeding and hydratation, as well as maintaining water balance, and also disturbs cooperation, worsening the course and prognosis of the primary disease. It is believed that consciousness disorders are one of the most difficult diagnostic problems and the most difficult therapy problem among psychotic disorders. So far in Poland there have been no screening evaluation tools to assess the occurrence of confusion on the somatic basis. The purpose of this paper is to introduce the Polish translation of the widely used scale to assess consciousness disorders, intended also for middle personnel of health care – Confusion Assessment Method (CAM). Numerous studies over 16 years established the position of CAM as an exceptionally effective standardized diagnostic test, specifying the sensitivity of 94-100%, specificity from 90-95%, positive predictive value of 91-94%, negative predictive value of 90-100%. The questionnaire and instructions of its interpretation have been translated by doctors with active help from the original creators of CAM. Further studies are required in order to validate and determine the effectiveness of the newly formed diagnostic tool.